2018
DOI: 10.1016/j.antiviral.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram can inhibit MERS and SARS coronavirus papain-like proteases via different modes

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV) emerged in southern China in late 2002 and caused a global outbreak with a fatality rate around 10% in 2003. Ten years later, a second highly pathogenic human CoV, MERS-CoV, emerged in the Middle East and has spread to other countries in Europe, North Africa, North America and Asia. As of November 2017, MERS-CoV had infected at least 2102 people with a fatality rate of about 35% globally, and hence there is an urgent need to identify antiviral drugs that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
210
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 235 publications
(218 citation statements)
references
References 38 publications
3
210
1
4
Order By: Relevance
“…This drug was reported to inhibit the activity of methyltransferase [93], kinase [94], and urease [94], all by reacting with cysteine residues, suggesting broad-spectrum characteristics [95]. Notably, disulfiram (47) has been reported as an allosteric inhibitor of MERS-CoV PL pro [95]. It was suggested that the administration of 41 together with compound 44 and/or 45, could synergistically inhibit MERS-CoV papain-like protease [95].…”
Section: Mers-cov and Sars-cov Pl Proteases Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This drug was reported to inhibit the activity of methyltransferase [93], kinase [94], and urease [94], all by reacting with cysteine residues, suggesting broad-spectrum characteristics [95]. Notably, disulfiram (47) has been reported as an allosteric inhibitor of MERS-CoV PL pro [95]. It was suggested that the administration of 41 together with compound 44 and/or 45, could synergistically inhibit MERS-CoV papain-like protease [95].…”
Section: Mers-cov and Sars-cov Pl Proteases Inhibitorsmentioning
confidence: 99%
“…Notably, disulfiram (47) has been reported as an allosteric inhibitor of MERS-CoV PL pro [95]. It was suggested that the administration of 41 together with compound 44 and/or 45, could synergistically inhibit MERS-CoV papain-like protease [95].…”
Section: Mers-cov and Sars-cov Pl Proteases Inhibitorsmentioning
confidence: 99%
“…Several coronaviral PL pro inhibitors have been identified in previous studies (Chen et al, 2009;Cheng et al, 2015;Chou et al, 2008;Lin et al, 2018;Ratia et al, 2008). In the present study, these compounds were screened to determine whether they can inhibit PEDV PL2 pro (Table 2).…”
Section: The Inhibition Of Pedv Pl2promentioning
confidence: 99%
“…Like other CoVs, PEDV depends on its own proteases, including main protease (M pro ) and papain-like protease (PL pro ) to cleave the polyprotein, and alpha CoVs have both papain-like protease 1 (PL1 pro ) and papain-like protease 2 (PL2 pro ) (Lee, 2015;Wojdyla et al, 2010). Polyprotein cleavage is required for viral maturation and thus these proteases are ideal antiviral targets (Bacha et al, 2008;Cheng et al, 2015;Chou T et al, 2008;Kumar et al, 2017;Lin et al, 2018;Park et al, 2012;Ratia et al, 2008;Wu et al, 2006). Furthermore, in contrast to highly variable spike proteins targeted by antibodies (Li et al, 2005(Li et al, , 2017; Wang et al, 2013;Wu et al, 2009), proteases with more conserved structure and catalytic function may serve as a general target across different CoVs Bailey-Elkin et al, 2014;Chou et al, 2014;Ho et al, 2015;Ratia et al, 2006;Yang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation